Resolving the disc–halo degeneracy – I: a look at NGC 628 - Aniyan, S; Freeman, K.C.; Arnaboldi, M.; Gerhard, O.E.; Coccato, L.; Fabricius, M.; Kuijken, K.; Merrifield, Michael R.; Ponomareva, A.A. (Oxford University Press, 2018)
The decomposition of the rotation curve of galaxies into contribution from the disc and dark halo remains uncertain and depends on the adopted mass-to-light ratio (M/L) of the disc. Given the vertical velocity dispersion of stars and disc scale height, the disc surface mass density and hence the M/L can be estimated. We address a conceptual problem with previous measurements of the scale height and dispersion. When using this method, the dispersion and scale height must refer to the same population of stars. The scale height is obtained from near-infrared (IR) studies of edge-on galaxies and is weighted towards older kinematically hotter stars, whereas the dispersion obtained from integrated light in the optical bands includes stars of all ages. We aim to extract the dispersion for the hotter stars, so that it can then be used with the correct scale height to obtain the disc surface mass density. We use a sample of planetary nebulae (PNe) as dynamical tracers in the face-on galaxy NGC 628. We extract two different dispersions from its velocity histogram – representing the older and younger PNe. We also present complementary stellar absorption spectra in the inner regions of this galaxy and use a direct pixel fitting technique to extract the two components. Our analysis concludes that previous studies, which do not take account of the young disc, underestimate the disc surface mass density by a factor of ∼2. This is sufficient to make a maximal disc for NGC 628 appear like a submaximal disc.